2015
DOI: 10.3892/ol.2015.3041
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo hepatectomy and partial liver autotransplantation for hepatoid adenocarcinoma: A case report

Abstract: Abstract.We previously reported the case of a 56-year-old male who underwent surgical treatment for gastric hepatoid adenocarcinoma and splenic metastasis. The present study reports the case of the same patient who underwent successful ex vivo hepatectomy and partial liver autotransplantation. Computed tomography scans demonstrated that the tumor was located in the left and caudate lobes of the liver, with hepatic vein and inferior vena cava involvement, and right portal vein compression. To clarify the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Radical surgery in combination with adjuvant chemotherapy is regarded as the optimal treatment approach (2). Gastric and liver metastasis resection is occasionally performed for palliation in advanced/ metastatic HAS patients (85). And it was suggested that salvage surgery following chemotherapy could achieve curative resection of HAS with portal vein tumor thrombus (PVTT) (70).…”
Section: Treatment Surgerymentioning
confidence: 99%
“…Radical surgery in combination with adjuvant chemotherapy is regarded as the optimal treatment approach (2). Gastric and liver metastasis resection is occasionally performed for palliation in advanced/ metastatic HAS patients (85). And it was suggested that salvage surgery following chemotherapy could achieve curative resection of HAS with portal vein tumor thrombus (PVTT) (70).…”
Section: Treatment Surgerymentioning
confidence: 99%
“…The liver can safely tolerate total vascular occlusion for only approximately 60-90 minutes under normal temperature via conventional Pringle hepatic inflow occlusion 9. The blocking time is short but may cause residual liver ischemia, hepatic vein and inferior vena cava bleeding, multiple organ failure, and other complications 10,11. Liver transplantation was performed in this patient with total hepatic vascular occlusion at low temperature.…”
mentioning
confidence: 96%
“…Anecdotally, Wang et al41 recently described a 56-year-old male with progressive therapy-resistant metachronous liver metastases, as judged by increased biomarker levels (CEA and AFP), despite transcatheter arterial chemoembolization (TACE) and radiofrequency ablation. Sorafenib had to be stopped due to early adverse reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Sorafenib had to be stopped due to early adverse reactions. The patient underwent ex vivo hepatectomy and a partial liver autotransplantation, and 20 months after the liver autotransplantation, he was reported to be relapse-free and still alive 41…”
Section: Resultsmentioning
confidence: 99%